A Comparative Study of Leptin, Oxidant/Antioxidant Status and Some Trace Elements in Women of Healthy Control and Unexplained Infertility in Basrah-Iraq - Adnan Jassim Mohammed Al-Fartosy; Nadhum Abdulnabi Awad; Rsha Abdulradha Mahmood (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: To date, there is no study regarding women with unexplained infertility in the province of Basrah, Iraq. This study was conducted to compare the level of leptin, oxidant/antioxidant status, and some trace element levels in women of healthy control and unexplained infertility.METHODS: From total 96 women subjects, 32 subjects had primary unexplained infertility, 31 had secondary unexplained infertility, while 33 fertile women were taken as controls. The body mass index (BMI) of subjects was calculated with standard procedures. The level of fasting serum leptin, luteinizing hormone (LH), follicle stimulating hormone (FSH), prolactin (PRL), thyroid-stimulating hormone (TSH), 4-hydroxynonenal (4-HNE), lipid hydroperoxide (LOOH), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and the total antioxidant capacity (TAC) were determined by enzyme-linked immunosorbent assay (ELISA) methods. Magnesium (Mg) and zinc (Zn) were measured by flame, copper (Cu) by flameless atomic absorption spectrometry, while Selenium (Se) in whole blood was determined using hydride generation method.RESULTS: Non-significant changes (p>0.05) were seen in the level of BMI, leptin, TSH, FSH, LH and LH/FSH ratio. Level of 4-HNE, LOOH and Cu were significantly increased (p<0.01), while level of GSH, SOD, CAT, TAC, Se, Zn and Mg were significantly decreased (p<0.01) in primary and secondary type of unexplained infertility, compared to control.CONCLUSION: Serum leptin hormone is significantly associated with BMI and physical activity in both groups. The significant difference in oxidant/antioxidants status between unexplained infertile and fertile women may suggests a possible additional role of oxidative stress mechanisms in pathophysiology of unexplained infertility.KEYWORDS: unexplained infertility, leptin, oxidative stress, antioxidants, trace elements